"Who is our real enemy?" internalized racism in the Puerto Rican diaspora and the role of political education within community health intervention. (October 2022) - Mullany, Anna; Barbieri, Marielena; Smith, Stevaughn; Gubrium, Aline; Valdez, Luis A.
Abstract: Rationale: Puerto Ricans experience disproportionately high levels of emotional distress and co-occurring adverse health outcomes. Our study sought to elicit Puerto Rican men's perceptions of health disparities while centering dialogue on stressors, coping mechanisms, and general well-being. This paper focuses on one pronounced finding in our study, that of internalized racism and the effect it has on both individual well-being and intra-group cohesion. A significant gap within racial health disparity work is the role of internalized racism and its connection to psychological distress, ruptures in social unity, and resulting ill-health of racial and ethnic populations. Based on this, we probed this particular finding to further understand internalized racism within this Puerto Rican population. Methods: Using a hybrid thematic analysis approach, this study presents qualitative findings from in-depth interviews with Latino (92.5% Puerto Rican) men living in Springfield, Massachusetts and conducted between October 2019 and January 2020. Results: Our findings reveal a duality throughout: The acceptance and propagation of negative Latinx stereotypes and consequent intragroup division exists alongside expressions of community pride and desire for Latinx unity. This duality is analyzed by using W.E.B. Du Bois's theory of double consciousness. Double consciousness not only explains the self-disparagement toward oneself and one's own racial and ethnic group, but also elucidates a liberatory pathway toward political consciousness and well-being. The concept of "second sight" within double consciousness is particularly germane, speaking to one's awakening to the learned self-subjugation imposed by White supremacy. Conclusions: Internalized racism contributes to the persistent propagation of disparate health burdens in minoritized communities. Remediation can and should include community-led frameworks for the development of efficacious multilevel health interventions. The Young Lords community health activism provides such a model. These findings provide viable evidence-based examples of how the academy can synergize with community-led efforts to achieve collective agency. Highlights: Internalized racism is a key contributor to emotional distress and intragroup cohesion. Men repeated disparaging Latinx stereotypes alongside a desire for unity. Research and community-led efforts can synergize toward collective agency and equity. Critical praxis counters individual "self-help" public health initiatives. Internalized racism can be tackled by engaging in community struggle and collectivity.